Structural optimization and parametric study of offshore wind turbine jacket substructure - Tai, Kang (2014)
Studies were conducted on a bottom fixed offshore wind turbine with jacket type substructure, including structural optimization and parametric studies for a newly developed three-legged jacket. The four-legged jacket adapted for the NREL 5MW reference turbine within the IEA Task 30 OC4 project was selected as the reference support structure design. Coupled aero-hydro-servo-elastic simulation was carried out in the time-domain to model the dynamic response of the turbine. Fatigue (FLS) and ultimate limit state (ULS) analyses were performed for the substructure members. By comparing against the reference model, the three-legged designs were iteratively optimized to obtain Pareto optimal designs (with lowest material consumption). Under the load cases studied, the three-legged jacket can save up to 55 per cent (LC 5.6) and 13 per cent (LC 5.7) of structural mass and is feasible as an interesting alternative to the four-legged jacket. Further analyses were carried out to evaluate both design options in terms of structural stability and vibrational frequencies. Finally, parametric studies were carried out to investigate the sensitivity of the performance of the jacket substructures with respect to different load cases, loading directionality, and wind-wave misalignment. It is concluded that wind-wave misalignment effects can be neglected, but directionality effects can lead to differences in joint fatigue lifetimes of up to 60 per cent. It is therefore important to account for these effects in the design phase.